Clinical and immunological characteristics of HIV/syphilis co-infected patients following long-term antiretroviral treatment - Wu, Yuanni; Lu, Lianfeng; Song, Xiaojing; Liu, Xiaosheng; Yang, Yang; Chen, Ling; Tang, Jia; Han, Yang; Lv, Wei; Cao, Wei; Li, Taisheng (Frontiers in Public Health, 2024)
Objective This study aims to analyze the efficacy of anti-syphilis treatment and the impact of syphilis events on HIV virology and immunology in HIV/syphilis co-infected patients on long-term antiretroviral therapy (ART) and to investigate the incidence and factors of syphilis recurrence/re-infection/serofast state. The insights derived from this investigation can potentially guide strategies for preventing and managing syphilis and AIDS. Methods A retrospective case–control study was conducted at the AIDS clinic of Peking Union Medical College Hospital from January 2003 to December 2022. The study involved 86 HIV/syphilis co-infected patients and 86 HIV mono-infected patients matched based on age, baseline CD4 + T cell counts, and viral load. We examined the clinical characteristics of HIV/syphilis co-infected patients, evaluated the efficacy of anti-syphilis treatment, and analyzed the dynamic changes in HIV virology and immunology. The Generalized Estimating Equations (GEE) model investigated the factors associated with HIV/syphilis co-infection and syphilis recurrence/reinfection/serofast state. Results Syphilis serofast state was observed in 11.6% (10/86) of HIV/syphilis co-infected patients after treatment, and 33.7% (29/86) had syphilis recurrence or re-infection. The overall effectiveness of syphilis treatment stood at 76.8% (63/82). Notably, the effectiveness of syphilis treatment displayed a significant correlation with baseline syphilis titers exceeding 1:128 (p = 0.003). Over the 10-year follow-up period on ART, the HLA-DR + CD8+/CD8 + % levels in the HIV/syphilis co-infected group were markedly higher than those in the HIV mono-infected group (p < 0.05). However, no significant differences were observed between the two groups regarding HIV viral load, CD4+ T cell counts, CD8+ T cell counts, CD4/CD8 ratio, and CD38 + CD8+/CD8 + % (p > 0.05). GEE analysis model revealed that elevated HLA-DR + CD8+/CD8 + % levels were associated with HIV/syphilis co-infection (OR = 1.026, 95% CI = 1.007–1.046; p = 0.007) and syphilis recurrence/reinfection/serofast state (OR = 1.036, 95% CI = 1.008–1.065; p = 0.012). Conclusion While HIV/syphilis co-infected patients typically receive adequate treatment, the incidence of syphilis recurrence and reinfection remain notably elevated. A heightened HLA-DR + CD8+/CD8+ % is a notable risk factor for HIV/syphilis co-infection and syphilis recurrence/reinfection/serofast state. Therefore, it is advisable to reinforce health education efforts and ensure regular follow-ups for people living with HIV undergoing ART to monitor syphilis infection or increased risk of syphilis infection.